THE EFFECT OF TRAINING EFFECTIVENESS ON INDIVIDUAL WORK PERFORMANCE IN BUSINESS ORGANIZATIONS IN CAMBODIA - By, Loeung (Srawung: Journal of Social Sciences and Humanities, 2024)
On-the-job training or off-the-job training are considered training effectiveness which is very crucial for all employees to have earned more skills and knowledge to improve work performance for effective outcomes. Since some employers are not much concerned about training programs for their employees in business organizations which result in poor work performance. Therefore, this study aims to measure the training effectiveness which impacts on individual work performance in business organizations in Cambodia. Quantitative research has been employed in this study with descriptive and inferential data were analyzed. Simple and multiple regressions are used in order to test the training effectiveness variables on individual work performance. The study has constructed the valid questionnaires to survey 200 participants with different business organizations in Cambodia. A regression analysis reveals that training significantly influences individual work performance. All training variables, including style, content, environment, schedule, and materials, showed a positive relationship with performance. Training materials and training content have had positive effects on individual work performance. The study emphasizes the importance of investing in well-rounded training programs that consider various aspects of delivery and content. The study's value lies in its demonstration of how to apply successful aspects of training programs to improve individual work performance in business firms. Eventually, the study has suggested that the leaders of business organizations should consider the efficient techniques of organizing training programs for their employees.